2013
DOI: 10.1177/2050312113499912
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin ameliorates the progression of atherosclerosis via down regulation of the inflammatory and oxidative pathways

Abstract: Back ground:Atherosclerosis is the major cause of death. The most common risk factors are hyperlipidemia, diabetes, and other factors like chronic infection and inflammation.Objective:This study was undertaken to assess the effect of sitagliptin on atherosclerosis via interfering with inflammatory and oxidative pathways.Materials and Methods:A total of 18 local domestic male rabbits were included in this study. The animals were randomly divided into three groups (6 rabbits in each group): Group I normal were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…These findings agree with a previous study by Najah et al [ 21 ]. Treatment with Sitagliptin significantly reduced the levels of TC, TG, and LDL compared to the atherogenic group, consistent with the results of Sahar et al [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings agree with a previous study by Najah et al [ 21 ]. Treatment with Sitagliptin significantly reduced the levels of TC, TG, and LDL compared to the atherogenic group, consistent with the results of Sahar et al [ 15 ].…”
Section: Discussionsupporting
confidence: 90%
“…Sitagliptin, a selective dipeptidyl peptidase-4 (DPP-4) inhibitor, has shown significant success as a monotherapy or in combination with metformin for managing type 2 diabetes by blocking the breakdown of GLP-1 and glucose-dependent insulinotropic polypeptide, which increases their beneficial effects [ 14 ]. In addition to managing diabetes, incretin enhancers such as sitagliptin may have positive effects on diabetes pathophysiology and prevent major consequences like atherosclerosis [ 15 ]. Recent research by Wenbin et al shows that sitagliptin can decrease hepatic steatosis by increasing autophagy in ob/ob mice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 35 The anti-inflammatory effect of quercetin has been proved in both animal and human studies, 36 and STN has also been shown to downregulate some inflammatory pathways. 37 Adding these effects together can explain the significant decrease in the level of CRP produced by the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sitagliptin in previous studies has proven to have anti-atherosclerotic activity related to its ability to decrease lipid accumulation, in addition to the antioxidant and anti-inflammatory activities that aid in inhibiting the progress of atherosclerosis. 30 , 37 Quercetin also has been proven to inhibit LDL oxidation 42 and protect against atherosclerosis, 43 this can explain the effectiveness of the aforementioned combination in attenuating the atherogenic index and protecting the cardiac tissue from the deleterious effects of doxorubicin. Histopathological findings of the present study support the effectiveness of QC and STN together in reducing cardiac injury induced by DOX.…”
Section: Discussionmentioning
confidence: 99%
“…The anti‐atherosclerotic effects of sitagliptin have tight correlations with suppression of lipid accumulation and anti‐platelet effects, which were observed in either diabetic patients or experimental models . In hyperlipidaemic rabbits, the progression of atherosclerosis was postponed by sitagliptin treatment via reducing the production of lipid profiles . Furthermore, the regulation of platelet by sitagliptin was also reported, which might propose a potential role in the anti‐atherosclerotic of sitagliptin.…”
Section: Cardiovascular Protective Effects Of Sitagliptinmentioning
confidence: 96%